Editorial Introduction and "Pre-Raphaelitism and Australia" - Tasker, Meg; Inglis, Alison (Australasian Journal of Victorian Studies, 2019)
Overview of the origins and contents of the issue, Acknowledgements, and a short essay providing an overview of the study of Pre-Raphaelitism in Australia.